2018
DOI: 10.1080/10715762.2018.1504293
|View full text |Cite
|
Sign up to set email alerts
|

pLG72 induces superoxide radicals via interaction and aggregation with SOD1

Abstract: G72 has been characterised as a susceptibility gene that can have wide-ranging effects in a number of neurodegenerative diseases, including schizophrenia and major depression. Indeed, its product, pLG72, is a potential serum biomarker for schizophrenia. Previous transcriptomic and biochemical studies have indicated that pLG72 may induce the production of mitochondrial reactive oxygen species (ROS), resulting in cell damage. Here, we investigated the mechanism of pLG72 by transfecting a human U87 glioblastoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…It is also active against superoxide radical and hydrogen peroxide in both the cytoplasm and mitochondria therefore its up-regulation as result of Chlorella vulgaris supplementation indicated complete cellular protection. Sod1 is also involved in pharmacokinetic and reactive oxygen species detoxification pathways hence the microalga is a drug candidate in development of therapeutic solution for oxidative stress attenuation [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…It is also active against superoxide radical and hydrogen peroxide in both the cytoplasm and mitochondria therefore its up-regulation as result of Chlorella vulgaris supplementation indicated complete cellular protection. Sod1 is also involved in pharmacokinetic and reactive oxygen species detoxification pathways hence the microalga is a drug candidate in development of therapeutic solution for oxidative stress attenuation [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Increased pLG72 protein levels induced mitochondrial fragmentation (increased number of mitochondria/mm of the dendritic tree along the dendritic shafts) without inducing apoptosis in the COS-7 cell line and primary neurons and changed mitochondrial morphology (the vesicular mitochondria were more mobile, possibly delivered more rapidly to sites of intense growth) and dendritic branching in primary hippocampal neurons (within the period of active dendritogenesis only) [ 38 ]. Interestingly, pLG72 overexpression affected gene expressions of several mitochondrial-related proteins and increased ROS production in U87 glioblastoma cells, a rise quenched by the general ROS quencher Tempol [ 47 ]. The same work reported the co-localization of ectopically expressed pLG72 with superoxide dismutase 1 (SOD1, EC 1.15.1.1), resulting in SOD1 aggregation and partial inactivation, and in decreased cell proliferation.…”
Section: Putative Biological Roles Of Plg72mentioning
confidence: 99%
“…Recultured plG72 cells were compared with normal cells. The interaction between plG72 and SOD1 was detected by CoralHue fluorescence tracing [13]. It has been found that plG72 can cause SOD1 aggregation and reduce the content of SPD1.…”
Section: How the Daoa Influence The Schizophreniamentioning
confidence: 99%